The Effect of Physical Activity on Children's Logical-Mathematical Intelligence - Nofi Marlina Siregar; Eka Fitri Nofita Sari; Dinan Mitsalina (Program Studi Magister Pendidikan Anak Usia Dini, 2023)
Research between physical activity and cognitive work in children is still relatively rare and inconsistent, even though children's motor development and cognitive learning are related to positive effects on academic work. This study aims to determine the increase in mathematical logical intelligence of early childhood through physical activity. This is action research. This type of research was a sequential exploratory design. Data analysis in this study used a combined quantitative and qualitative analysis (Mix Method). The results showed increasing logical mathematics intelligence in DKI Jakarta's childhood. The initial assessment results showed that the average value of the child's logical mathematics intelligence was 28 and then increased to 57 in the final assessment of cycle 1 and continued to increase to 78 in the final assessment of cycle 2. Physical activity learning with games strategies increasing the logical mathematics intelligence in childhood in Jakarta Kindergarten. Future research is expected to examine more childhood intelligence with many respondents. Keywords: early childhood, physical activity, logical-mathematics intelligence References: Andriyani, FD, Biddle, SJH, Arovah, NI, & de Cocker, K. (2020). Physical activity and sedentary behavior research in Indonesian youth: A scoping review. International Journal of Environmental Research and Public Health,17(20), 1–15. https://doi.org/10.3390/ijerph17207665 Aubert, S., Brazo-sayavera, J., González, SA, Janssen, I., Manyanga, T., Oyeyemi, AL, Picard, P., Sherar, LB, Turner, E., & Tremblay, MS (2021). Global prevalence of physical activity for childhood and adolescents; inconsistencies , research gaps , and recommendations : a narrative review. 1–11. Azman, KF, & Zakaria, R. (2022). Recent Advances on the Role of Brain-Derived Neurotrophic Factor (BDNF) in Neurodegenerative Diseases. International Journal of Molecular Sciences, 23(12). https://doi.org/10.3390/ijms23126827 Beck, MM, Lind, RR, Geertsen, SS, Ritz, C., Lundbye-Jensen, J., & Wienecke, J. (2016). Motor-enriched learning activities can improve mathematical performance in preadolescent childhood. Frontiers in Human Neuroscience, 10(DEC2016). https://doi.org/10.3389/fnhum.2016.00645 Bunketorp Käll, L., Malmgren, H., Olsson, E., Lindén, T., & Nilsson, M. (2015). Effects of a Curricular Physical Activity Intervention on Childhood's School Performance, Wellness, and Brain Development. Journal of School Health, 85(10), 704–713. https://doi.org/10.1111/josh.12303 Chaddock-Heyman, L., Erickson, KI, Voss, MW, Knecht, AM, Pontifex, MB, Castelli, DM, Hillman, CH, & Kramer, AF (2013). The effects of physical activity on functional MRI activation associated with cognitive control in childhood: A randomized controlled intervention. Frontiers in Human Neuroscience, 7(FEB), 1–13. https://doi.org/10.3389/fnhum.2013.00072 Colucci-D'amato, L., Speranza, L., & Volpicelli, F. (2020). Neurotrophic factor bdnf, physiological functions and therapeutic potential in depression, neurodegeneration and brain cancer. International Journal of Molecular Sciences, 21(20), 1–29. https://doi.org/10.3390/ijms21207777 Daly-Smith, AJ, Zwolinsky, S., McKenna, J., Tomporowski, PD, Defeyter, MA, & Manley, A. (2018). Systematic review of acute physically active learning and classroom movement breaks on childhood's physical activity, cognition, academic performance and classroom behavior: Understanding critical design features. BMJ Open Sport and Exercise Medicine, 4(1), 1–16. https://doi.org/10.1136/bmjsem-2018-000341 Deer, LBK, Hastings, PD, & Hostinar, CE (2020). The Role of Childhood Executive Function in Explaining Income Disparities in Long-Term Academic Achievement. Child Development, 91(5), e1046–e1063.https://doi.org/10.1111/cdev.13383 Fischer, U., Suggate, SP, & Stoeger, H. (2020). The Implicit Contribution of Fine Motor Skills to Mathematical Insight in Early Childhood. Frontiers in Psychology, 11. https://doi.org/10.3389/fpsyg.2020.01143 Flores, P., Coelho, E., Mourão-Carvalhal, MI, & Forte, P. (2023). Association between motor and math skills in preschool childhood with typical development: Systematic review. Frontiers in Psychology, 14(February), 1–23. https://doi.org/10.3389/fpsyg.2023.1105391 Gao, Z., Chen, S., Sun, H., Wen, X., & Xiang, P. (2018). Physical Activity in Childhood's Health and Cognition. BioMed Research International, 2018. https://doi.org/10.1155/2018/8542403 Gomez-Pinilla, F., & Hillman, C. (2013). The influence of exercise on cognitive abilities. Comprehensive Physiology, 3(1), 403–428. https://doi.org/10.1002/cphy.c110063 Grieco, LA, Jowers, EM, Errisuriz, VL, & Bartholomew, JB (2017). Response Study for Elementary Student Time on Task. 98–103. https://doi.org/10.1016/j.ypmed.2016.05.021.Physically Ha, AS, Ng, JYY, Lonsdale, C., Lubans, DR, & Ng, FF (2019). Promoting physical activity in childhood through family-based intervention: Protocol of the “Active 1 + FUN” randomized controlled trial 11 Medical and Health Sciences 1117 Public Health and Health Services 17 Psychology and Cognitive Sciences 1701 Psychol. BMC Public Health, 19(1), 218. https://bmcpublichealth.biomedcentral.com/articles/10.1186/s12889-019-6537-3 Hajar, MS, Rizal, H., & Kuan, G. (2019). Effects of physical activity on sustained attention: A systematic review. Scientia Medica, 29(2), 1–15. https://doi.org/10.15448/1980-6108.2019.2.32864 Hildebrandt, S. (2018). Executive functions. Neuropsychology for Occupational Therapists: Cognition in Occupational Performance, 165–176. https://doi.org/10.1002/9781119557036.ch10 Human, department oh health and, & Services. (2016). Physical activity guidelines for Americans 2nd edition. The Oklahoma Nurse, 53(4), 25. https://doi.org/10.1249/fit.0000000000000472 Janssen, I., & LeBlanc, AG (2010). Systematic review of the health benefits of physical activity and fitness in school-aged childhood and youth. International Journal of Behavioral Nutrition and Physical Activity, 7.https://doi.org/10.1186/1479-5868-7-40 Krisiyanto. (2020). PTK (classroom action research) model Kemmis and Mc Taggrat (pp. 12–15). Macdonald, K., Milne, N., Orr, R., & Pope, R. (2020). Associations between motor proficiency and academic performance in mathematics and reading in year 1 school childhood: A cross-sectional study. BMC Pediatrics, 20(1). https://doi.org/10.1186/s12887-020-1967-8 Mahardika, GA (2021). The Relationship between Corner Learning Outcomes and Mathematics Learning Outcomes. Undiksha Journal of Sports Science, 9(2), 99. https://doi.org/10.23887/jiku.v9i2.37361 Miranda, M., Morici, JF, Zanoni, MB, & Bekinschtein, P. (2019). Brain-Derived Neurotrophic Factor: A Key Molecule for Memory in the Healthy and the Pathological Brain. Frontiers in Cellular Neuroscience, 13(August), 1–25. https://doi.org/10.3389/fncel.2019.00363 Organização Mundial de Saúde. (2022). World health statistics 2022 (Monitoring health of the SDGs). In Monitoring the health of the SDGs. http://apps.who.int/bookorders. Organization, world health. (2020). Physical activity. November, 1–9. Owen, KB, Parker, PD, Van Zanden, B., MacMillan, F., Astell-Burt, T., & Lonsdale, C. (2016). Physical Activity and School Engagement in Youth: A Systematic Review and Meta-Analysis. Educational Psychologist, 51(2), 129–145. https://doi.org/10.1080/00461520.2016.1151793 Reikerås, E., Moser, T., & Tønnessen, FE (2017). Mathematical skills and motor life skills in toddlers: do differences in mathematical skills reflect differences in motor skills? European Early Childhood Education Research Journal, 25(1), 72–88. https://doi.org/10.1080/1350293X.2015.1062664 Sember, V., Jurak, G., Kovač, M., Morrison, SA, & Starc, G. (2020). Childhood's Physical Activity, Academic Performance, and Cognitive Functioning: A Systematic Review and Meta-Analysis. Frontiers in Public Health, 8(July). https://doi.org/10.3389/fpubh.2020.00307 Shi, P., Tang, Y., Zhang, Z., Feng, X., & Li, C. (2022). Effects of Physical Exercise in Real-World Settings on Executive Function of Typical Childhood and Adolescents: A Systematic Review. Brain Sciences, 12(12).https://doi.org/10.3390/brainsci12121734 Silakarma, D., & Sudewi, AAR (2019). The role of brain-derived neurotrophic factor (BDNF) in cognitive functions. Bali Medical Journal, 8(2), 518–525. https://doi.org/10.15562/bmj.v8i2.1460 Stillman, CM, Cohen, J., Lehman, ME, & Erickson, KI (2016). Mediators of physical activity on neurocognitive function: A review at multiple levels of analysis. Frontiers in Human Neuroscience, 10(DEC2016), 1–17.https://doi.org/10.3389/fnhum.2016.00626 Tomaczkowski, L., & Klonowska, J. (2020). Physical activity of school childhood and youth. Baltic Journal of Health and Physical Activity, 12(2), 83–87. https://doi.org/10.29359/bjhpa.12.2.09 Vorkapic, CF, Alves, H., Araujo, L., Joaquim Borba-Pinheiro, C., Coelho, R., Fonseca, E., Oliveira, A., & Dantas, EHM (2021). Does Physical Activity Improve Cognition and Academic Performance in Childhood? A Systematic Review of Randomized Controlled Trials. Neuropsychobiology, 80(6), 454–482. https://doi.org/10.1159/000514682 Zulherma, Z., & Suryana, D. (2019). The Role of the Executive Function Brain in the Development of Early Childhood Cognitive Ability in the 2013 Curriculum. Journal of Tambusai Education, 3(2), 648–656.